The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00280-019-03920-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of CT-P6 versus reference trastuzumab in HER2-positive early breast cancer: updated results of a randomised phase 3 trial

Abstract: PurposeNeoadjuvant CT-P6, a trastuzumab biosimilar, demonstrated equivalent efficacy to reference trastuzumab in a phase 3 trial of HER2-positive early-stage breast cancer (EBC) (NCT02162667). We report post hoc analyses evaluating pathological complete response (pCR) and breast pCR alongside additional efficacy and safety measures.MethodsFollowing neoadjuvant treatment and surgery, patients received adjuvant CT-P6 or trastuzumab (6 mg/kg) every 3 weeks for ≤ 1 year.ResultsIn total, 271 and 278 patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 14 publications
7
38
0
12
Order By: Relevance
“…In the current study, neither CT-P6 nor RTZ showed serious cardiac toxicity pro les. No patients with EBC experienced a reduction in LVEF of < 50% in either treatment group, consistent with the low cardiotoxicity observed in patients with EBC treated with RTZ or CT-P6 in the neoadjuvant [16,21] and adjuvant [17,21] settings. In the current study, 2/38 (5.3%) patients with MBC experienced a decline in LVEF to < 50% with CT-P6, as did 4/65 (6.2%) patients in the RTZ group.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the current study, neither CT-P6 nor RTZ showed serious cardiac toxicity pro les. No patients with EBC experienced a reduction in LVEF of < 50% in either treatment group, consistent with the low cardiotoxicity observed in patients with EBC treated with RTZ or CT-P6 in the neoadjuvant [16,21] and adjuvant [17,21] settings. In the current study, 2/38 (5.3%) patients with MBC experienced a decline in LVEF to < 50% with CT-P6, as did 4/65 (6.2%) patients in the RTZ group.…”
Section: Discussionsupporting
confidence: 77%
“…[14,15] Approval was based in part on a phase III clinical trial in patients with operable HER2-positive EBC, which showed comparable safety and equivalent e cacy of CT-P6 and reference trastuzumab (RTZ) when administered in combination with docetaxel and uorouracil, epirubicin and cyclophosphamide (FEC). [16,17] Data from a 3-year follow-up study have subsequently con rmed that disease-free survival and OS are similar in patients treated with CT-P6 and RTZ. [18] Real-world studies are an important supplement to clinical trials, by revealing the long-term safety and effectiveness of drugs in broader patient populations, as well as in other settings and in combination with other treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Primary outcome of pathological CR and secondary outcome of ORR were found to be similar, as summarized in Table 1, with no clinically significant difference in toxicity. An updated analysis by Esteva et al 69 yielded no major differences at 1 year with regard to progressive disease and the number of patients who experienced a reduction in left-ventricular ejection fraction. Trastuzumab-dttb (also known as SB3) was approved based on a phase 3 study by Pivot et al, 70-72 which randomized patients to receive either SB3 or trastuzumab-EU in 800 patients with operable HER2-positive breast cancer.…”
Section: Trastuzumab Biosimilar In Breast Cancer and Gastric Cancermentioning
confidence: 99%
“…Trastuzumab-pkrb (also known as CT-P6) received approval based on a phase 3 study by Stebbing et al 68 , in 549 patients with operable HER2-positive breast cancer who received either CT-P6 or trastuzumab-US. 69 Patients received 4 cycles of CT-P6 or trastuzumab-US as neoadjuvant therapy in combination with docetaxel and another 4 cycles as adjuvant therapy in combination with FEC (fluorouracil, epirubicin, and cyclophosphamide). Primary outcome of pathological CR and secondary outcome of ORR were found to be similar, as summarized in Table 1, with no clinically significant difference in toxicity.…”
Section: Trastuzumab Biosimilar In Breast Cancer and Gastric Cancermentioning
confidence: 99%
“…Trastuzumab, the first recombinant humanised monoclonal antibody against HER2, has been widely used as one of the leading HER2-targeted agents. Recently, various trastuzumab biosimilars such as Herzuma (trastuzumab-pkrb) [ 16 , 17 ], Ogivri (trastuzumab-dkst) [ 18 ], Ontruzant (trastuzumab-dttb) [ 19 ], Trazimera (trastuzumab-qyyp) [ 20 ] and Kanjinti (trastuzumab-anns) [ 21 ] have been developed and approved. As these agents show efficacy and safety similar to trastuzumab, their use has become increasingly popular.…”
Section: Introductionmentioning
confidence: 99%